2022
DOI: 10.1002/jso.27056
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after repeat hepatectomy for colorectal liver metastases from the colorectal liver operative metastasis international collaborative (COLOMIC)

Abstract: Background Resection of colorectal liver metastasis (CLM) is beneficial when feasible. However, the benefit of second hepatectomy for hepatic recurrence in CLM remains unclear. Methods The Colorectal Liver Operative Metastasis International Collaborative retrospectively examined 1004 CLM cases from 2000 to 2018 from a total of 953 patients. Hepatic recurrence after initial hepatectomy was identified in 218 patients. Kaplan–Meier analysis was performed for overall survival (OS) and recurrence‐free survival (RFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…5 Despite the recent introduction of novel multidrug chemotherapeutic regimens and biological agents, repeat hepatectomy for the recurrent intrahepatic disease remains a safe treatment approach, providing a potential improvement in oncologic outcomes. [6][7][8][9] Prior studies have demonstrated a positive association between repeat hepatectomy and favorable long-term outcomes among patients experiencing a recurrence of previously resected CRLM. 10,11 For example, Sutton et al reported that patients who underwent repeat hepatectomy had a 47% reduction in the risk of death compared with individuals who received systemic chemotherapy, even after adjusting for various clinicopathological imbalances between the two groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Despite the recent introduction of novel multidrug chemotherapeutic regimens and biological agents, repeat hepatectomy for the recurrent intrahepatic disease remains a safe treatment approach, providing a potential improvement in oncologic outcomes. [6][7][8][9] Prior studies have demonstrated a positive association between repeat hepatectomy and favorable long-term outcomes among patients experiencing a recurrence of previously resected CRLM. 10,11 For example, Sutton et al reported that patients who underwent repeat hepatectomy had a 47% reduction in the risk of death compared with individuals who received systemic chemotherapy, even after adjusting for various clinicopathological imbalances between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network guideline recommends several treatment options for recurrent CRLM, including re‐resection, local therapy, and systemic chemotherapy 5 . Despite the recent introduction of novel multidrug chemotherapeutic regimens and biological agents, repeat hepatectomy for the recurrent intrahepatic disease remains a safe treatment approach, providing a potential improvement in oncologic outcomes 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…14 NCCN guidelines do not list CRS/HIPEC as a treatment option for colorectal cancer with PSD, 15 even though a recent phase III multicenter randomized trial demonstrated a 42-month median OS for complete cytoreduction of colorectal peritoneal carcinomatosis. 16 There are multiple studies reviewing outcomes of metastasectomy for colorectal liver disease [17][18][19][20] and for peritoneal surface metastases; [21][22][23][24] however, studies comparing the two are lacking. The goal of this article will be to review the current literature comparing outcomes between surgical management of colorectal liver metastases and colorectal PSD.…”
Section: Introductionmentioning
confidence: 99%
“…40,61,62 Um achado importante observado em nosso estudo foi o de que porcentagem similar de pacientes de ambos os grupos permaneceu livre de doença a longo prazo, o que também foi observado por outros autores, e denota o potencial de cura da reabordagem cirúrgica em casos selecionados. [63][64][65] Poucos autores avaliaram os resultados da reabordagem cirúrgica em pacientes com RP (≤ 6 meses) após a primeira hepatectomia. 66,67 Os estudos existentes mostram que este subgrupo de pacientes tem pior prognóstico.…”
Section: Discussionunclassified
“…Apesar disso, com citado anteriormente, nosso objetivo foi avaliar os resultados da rehepatectomia a partir de um estudo de "vida real', utilizando os critérios de seleção empregados na rotina clínica do Serviço.Acreditamos que a utilização de critérios de inclusão bem definidos, excluindo pacientes submetidos a hepatectomias em dois tempos, e ressecções não curativas sejam suficientes para as comparações pretendidas. Outro fator que pode ter impactado nossos resultados foi o pequeno número de pacientes, em especial, no subgrupo submetido à rehepatectomia por RP, o que pode ter influenciado na ausência de diferença na sobrevida quando comparada ao grupo RT, pelo aumento do erro beta.Apesar das limitações, acreditamos que tenhamos conseguido resultados consistentes e fidedignos, os quais demonstram os benefícios da rehepatectomia para pacientes selecionados com recorrências das MHCCR, sendo este um dos maiores estudos publicados sobre o tema 40,64,65.…”
unclassified